2018
DOI: 10.1016/j.jtho.2017.10.034
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression of Tumor Cells, Macrophages, and Immune Cells in Non–Small Cell Lung Cancer Patients with Malignant Pleural Effusion

Abstract: These results suggest that there might be an immune interaction between pleural effusion tumor cells and macrophages. The low intensity of PD-L1 expression in immune cells is associated with the poor survival of patients with lung cancer with malignant pleural effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
1
29
1
Order By: Relevance
“…They also found that low PD‐L1 expression in immune cells is associated with poor patients’ survival. They finally suggested that MPE could be used for PDL‐1 testing . A French group evaluated PD‐L1 tumour proportion score using 22C3 anti‐PD‐L1 antibody‐based laboratory developed tests (LDTs), from 70 paired biopsy and cytology samples including 30 samples from MPE.…”
Section: Implications Of New Therapies In Nsclcmentioning
confidence: 99%
See 4 more Smart Citations
“…They also found that low PD‐L1 expression in immune cells is associated with poor patients’ survival. They finally suggested that MPE could be used for PDL‐1 testing . A French group evaluated PD‐L1 tumour proportion score using 22C3 anti‐PD‐L1 antibody‐based laboratory developed tests (LDTs), from 70 paired biopsy and cytology samples including 30 samples from MPE.…”
Section: Implications Of New Therapies In Nsclcmentioning
confidence: 99%
“…A part from PDL1 expression, other biomarkers, such as tumour mutational burden (TMB) are emerging to predict the response to immunotherapy, and it would be interesting to determine whether MPE can be a tool, especially when there is no tumour tissue available.…”
Section: Implications Of New Therapies In Nsclcmentioning
confidence: 99%
See 3 more Smart Citations